سةرهةلَداني رِؤذنامةنووسيي كوردي و رِؤلَي لة ثةرةسةندني زمان و ئةدةبدا (Journal of the College of Languages (JCL), 2014)
Appearance of the Kurdish press in the Kurdish literature was affected by as set of both external and internal factors. The former was realized in the spreading of press and publications especially at the neighboring countries in the second half of the 19th century. The latter factors, external ones ,were concerned the political situations undergone by the Kurdish people who severely suffered injustice practiced by the Othman authority .All these reasons had driven the educated to migrate to search for more safe places to practice their cultural actions with absolute freedom. Consequently, the first newspaper was issued on 22/4/1898 in Cairo which pointed the birth of the Kurdish press inside and outside Kurdistan region which undertook major tasks in developing both language and literature. Based on the above, the present researcher has tempted to conduct a study entitled "Appearance of the Kurdish press and it Role in Developing Language and Literature" .At the scope of the language, the Kurdish press had begun to use the Arabic letters along with parsing sings in writing, and later on it began to use the Kurdish letters which are currently used. It also began to reduce using foreign words. Regarding literature, the Kurdish press had undergone the responsibility of modernizing literature through involving new literary types, especially in essay writing, story, and novel and other types. The researcher has adopted three models of press publications for the sake of identifying changes in each period of time since 1898 up to 1930:Kurdistan Newspaper "1898"Roj Kurd journal "1913"Zyan Newspaper "1930"